Mathematical Literacy in PjBL assisted by E-LKPD in terms of Self Concept - Amidi, Amidi; Kartono, Kartono; Mulyono, Mulyono; Pujiastuti, Emi (Universitas Negeri Semarang, 2024)
Mathematical literacy and self-concept have become crucial topics in 21st century learning. So that learning innovation and the use of technology need to be carried out to support students' abilities to face the challenges of globalization. The purpose of this study is to describe students' mathematical literacy in terms of self-concept. This study uses a sequential explanatory design. The population in this study was class VIII of one of the junior high schools in Semarang Regency in the 2022/2023 academic year. Subjects in this study were selected using a purposive sampling method based on high, medium and low self-concept categories. Collecting data through test techniques, questionnaire techniques, interviews, and observation. The results showed that the mathematical literacy of students with high self-concept categories was better than students with moderate and low self-concept categories. Students with high self-concept are able to fulfill all indicators of mathematical literacy well; students with moderate self-concepts are able to master the three indicators of literacy but are still unable to apply mathematical concepts, facts, and procedures and represent answers in real-world contexts; students with low self-concept are only able to identify and represent problems mathematically while other indicators have not been fulfilled properly.